OP-AMP based interface circuit for resistive sensor with lead-wire-resistance compensation - Kaewpoonsuk, Anucha; Katman, Ratchanoo; Rerkratn, Apinai (My University, 2019)
This paper presents a simple technique to implement the resistive sensor interface for remote measuring. The circuit is designed using a relaxation oscillator to generate a square wave signal. The time difference during charging and discharging a capacitor is directly proportional to the sensor’s resistance. The structure of the circuit is composed of two op-amps, three bipolar junction transistors, a capacitor, four fixed resistors and a variable resistor. Features of the proposed circuit are single-supply operation and direct interface with a microcontroller without an analog-to-digital converter. In addition, the lead-wire resistance is automatically compensated. When the resistance values of the sensor are varied in the range of 500-1500 O with lead-wire resistance values of 0-100 ω, the result of the circuit testing is found that the maximum error is approximately equal to 1.15% of full scale. The performance of the circuit is in accordance with principles proposed.
Keywords: Interface circuit; Op-amp; Remote measurement; Resistive sensors